Aid, growth and decentralization - Christian Lessmann; Gunther Markwardt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
This paper examines whether the federal structure of aid-receiving countries matters in explaining aid effectiveness. Following the decentralization theorem, the devolution of powers should increase aid effectiveness, since local decision-makers are better informed about local needs. At the same time, decentralization has reverse effects, e.g., through coordination problems, excessive regulation, administrative costs and local capture. Using panel data for up to 59 countries, we find that aid is less effective or even harmful in decentralized countries. Our results imply that donor countries should carefully consider how both anti-poverty instruments financial assistance and decentralization work together.
Keywords: O1; O2; O4; H7; 330; Foreign Aid; Growth; Decentralization